Analisis Faktor yang Berdampak pada Proftabilitas (Studi Kasus Pada Perusahaan Food & Beverage yang Terdaftar di Bursa Efek Indonesia) - Wulandari, Nona Novia; Istanti, Sri Layla Wahyu (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2025)
The goal of this research was to look at the impact of firm size, age, and leverage on the profitability of manufacturing companies joined on the IDX in the food and beverage subsectors period 2020 and 2022. Profitability was the dependent variable in this study, while the independent factors were company size, age, and leverage. From 2020 to 2022, the population consisted of 30 manufacturing enterprises in the Indonesian Stock Exchange’s food and beverage subsector (source: www.idx.com). Research data was collected using a specified technique. The sample was chosen using the purposive sampling method. The study sample comprised 23 firms and 69 observations. The data was analyzed using several linear analytic methodologies. According to the hypothesis testing results, firm size had an insignificant negative effect on profitability, but company age had an insignificant positive impact. And leverage had a considerable positive impact on profitability.